New-Onset Diabetes after Transplant (NODAT) - Maskey, R (Kathmandu University Medical Journal, 2015)
New onset diabetes mellitus after transplantation (NODAT) is a well known complication following solid organ transplantation and has been reported to occur in 4% to 25% of renal transplant recipients, 2.5% to 25% of liver transplant recipients, hepatitis C virus (HCV) infection between 40% and 60% and 2% to 53% of all solid organ transplants. This variation in the reported incidence may be because of lack of a universal agreement on the definition of NODAT, the duration of follow-up, and the presence of modifiable and non-modifiable risks factors. Moreover, reduced patient survival and accelerated graft loss have been reported with NODAT. In our country also there is increasing in number of kidney transplants patients and along with that there is chance of development of NODA. It is better to detect the NODATS early. So in this article I tried to presents an overview of the literature on the current diagnostic criteria for NODAT and discuss suggested risk factors for the development of NODAT, its potential pathogenic mechanisms, and its impact on post-transplant outcomes after solid organ transplantation.Kathmandu University Medical Journal Vol.12(4) 2014; 301-305